Medial mobile-bearing unicompartmental knee arthroplasty in young patients aged less than or equal to 50 years - Greco, N; Lombardi, A; Price, A; Berend, M; Berend, K (Elsevier, 2018)
Contemporary research has shown medial mobile-bearing unicompartmental knee arthroplasty to be an effective treatment in patients younger than 60 years; however, only one other study has specifically investigated unicompartmental arthroplasty outcomes in patients 50 years or younger. The purpose of this study was to determine the clinical outcomes and survivorship of medial mobile-bearing unicompartmental arthroplasty in this younger patient population.A retrospective review of patients undergoing primary unicompartmental knee arthroplasty using the Oxford partial knee from 2003 to 2014 in a single practice database was performed. Patients were included in the study if they were 50 years of age or younger with a primary diagnosis of anteromedial osteoarthritis and minimum clinical follow-up of 2 years. Patient clinical outcomes, function, and need for revision surgery were assessed.The study included 340 knees. Average patient age was 46.5 years, and the mean follow-up was 6.1 years. Patients demonstrated significant improvements (P < .05) in range of motion (114.5 v 116.9), University of California Los Angeles activity score (4.4 vs 5.6), Knee Society clinical (37.3 vs 86.5) and functional scores (58.8 v 79.8). Overall, 20 patients required reoperation, and the predicted survival rate was 96% at 6 years and 86% at 10 years. Aseptic loosening occurred in 7 patients at an average of 5.6 years postoperatively, while 4 patients required conversion to total knee arthroplasty because of arthritic progression at a mean time of 6.6 years. There were no revision procedures required due to polyethylene liner wear or breakage.Medial mobile-bearing unicompartmental arthroplasty should be considered as a treatment option in patients younger than 50 years of age suffering from anteromedial osteoarthritis of the knee.